Les blogs « extimes » : analyse sociologique de l’interactivité des blogs - Sébastien ROUQUETTE (Tic & Société)
The primary objective of this article is to understand the initial motivations of bloggers of personal blogs. The second is to explain the globally positive perception that bloggers have about reactions of the Internet users. Finally, four types of motivations dominate: give a testimony, reveal his(her) personality, give her opinion, write. The success of those blogs can thus be explained by the positive reactions received by bloggers about their blogs.